INTEGRATING ABC AND EVA TO EVALUATE INVESTMENT DECISIONS - N. Chiadamrong (Universitas Gadjah Mada, 2003)
The significance of investment is transparent in the world of competitive business. Traditional costing systems in which their emphasizes are for short term savings rather than long term benefits have shown some lacking in providing accurate and reliable cost data for the investment decisions. Activity-based Costing (ABC), which is developed to satisfy some of the weaknesses of the traditional costing systems, can provide valuable insights into the operating processes and come up with more accurate cost data. In this paper, ABC is used to provide significant information for investment decisions. Although, the ABC method provides accurate operating product costs, it does not identify which products are economic valued added creators and so contribute to companies’ wealth. This drawback can be overcome by applying Economic Value Added (EVA). The adoption of ABC and EVA can represent a considerable change in the managerial thinking and to corporate strategies and business performance.